The Territorial Availability and Diffusion of Broadband in Finland: Lessons From Finnish Broadband Policy - Timo Hirvonen; Lauri Frank (European Regional Science Association (ERSA), 2006)
Most countries dispose towards the development of the information society (IS). Due to increased political interest, there has also been a growing need to collect and compile IS statistics for informed decision-making. Thus, various indicators have been collected and different indices developed to measure IS, to monitor its development and to compare countries in terms of IS performance. Although there is no unambiguous definition of what IS is actually composed of, the availability and use of information and communications technology (ICT) is seen to be an established part of it. This article examines the case of one IS indicator: the measurement of the availability of broadband in Finland from the year 2001 to 2004. The focus is on the overall sensibility of the indicators approach, the evolution of territorial differences at different spatial scales, and the effectiveness of the broadband policy in Finland in years 2001-2004. The analysis shows that the indicators of the availability of broadband might be misleading for purposes of policy formulation and monitoring. The results also indicate that the Finnish broadband policy has resulted in regional differences and spatially uneven impacts in terms of availability. This article is an outgrowth of the ESPON project "Identification of Spatially Relevant aspects of the Information Society".
Keywords: 330